Tracer Study Alumni Jurusan Kebidanan Poltekkes Kemenkes Kupang Tahun 2014 - Bringiwatty Batbual; Ignasensia Dua Mirong (JURNAL INFO KESEHATAN, 2018)
In order to become a trendsetter in Midwifery education in Indonesia, the Midwifery Department of the Health Polytechnic MoH of Kupang constantly strives to improve the quality of graduates in order to have competencies that are reliable and professional in the field of midwifery. In line with the accreditation activities at the Midwifery Department that occur every 5 years, it is necessary to conduct a Tracer Study to identify related graduate competencies, the needs of the job market, and get an overview of the competencies needed by Midwifery graduates. This data is needed in order to improve the quality of learning and ultimately the quality of graduates. Through this Tracer Study, we want to know the opinions of stakeholders about the development of soft skills at the Midwifery Department. This Tracer Study focused on agency leadership on the competence of alumni of the Midwifery Department. Obtaining information about stakeholder perceptions of the competence of alumni of the Midwifery Department Health Polytechnic MoH of Kupang after entering the workforce in terms of aspects: integrity (ethics and morals), expertise based on science (professionalism, English language skills, communication skills, leadership/leadership, mastery of information technology, teamwork, self-development, overall quality assessment. Method: The method used is a survey method. Data obtained from questionnaires distributed to each health agency. Most stakeholders have a good perception (65.2%) of alumni in aspects assessed from 15 agencies, except in aspects of mastery of foreign languages / English which is still lacking. It is concluded that stakeholder assessment of the competence of alumni of the Midwifery Department Health Polytechnic MoH of Kupang is partly big has been able to meet the needs of stakeholders.